تطبيق لعبة الهمس المتسلسل لترقية مهارة الاستماع في المدرسة الثانوية ثنائية اللغة باتو - faiz, nur (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2021)
The role of language games in the learning process can help teachers achieve better language learning goals. Students become more enthusiastic and less bored. Not only improve intellectual abilities but also social skills. In this game, students do not only focus on listening skills but also on speaking and writing skills and even reading. This article aims to improve students' listening skills with the Whisper Chain game. This research uses a qualitative and field approach in MA Bilingual. The results of the study show the application of the Whisper Chain game as follows: giving vocabulary, listening to reading texts, discussing difficult vocabulary, and finally evaluating and strengthening the material using games. By implementing the Whisper Chain game: 1) Can improve students 'listening skills effectively because it is more applicable as well as students memorize verbal vocabulary, 2) Increase students' social intelligence and increase their attention in learning, 3) Make it easier for students to better understand the material and provide learning experiences.